A low‐profile circularly polarized dielectric patch antenna with bandwidth expansion. Issue 3 (4th January 2021) - Chen, Jian‐Xin; Wang, Xue‐Ying; Huang, Ye‐Xin; Yang, Ling‐Ling; Tang, Shi‐Chang
Abstract: A new technology for expanding the axial ratio (AR) bandwidth of the circularly polarized (CP) dielectric patch (DP) antenna while maintaining the low‐profile characteristic is proposed for the first time. By making full use of the multimode characteristic of the DP resonator, two pairs of degenerate modes (ie, TM101 and TM011, TM121 and TM211 ) are selected for the broadband design. The key to the proposed technology is that according to the EM field distribution of the two pairs of degenerate modes, four air holes are introduced in the DP and their position and size are elaborately designed to discriminately control the frequency of the two pairs of degenerate modes. Then, these modes become close and are merged to effectively expanding the AR bandwidth of the low‐profile CP DP antenna. For demonstration, a prototype centered at about 10 GHz is designed, fabricated, and measured. The measured results exhibit that the proposed CP DP antenna with a low profile of 0.07 λ 0 owns a 3 dB AR bandwidth of 9.7% and a peak gain of 7.66 dBic. Good agreement is observed between simulated and measured results.